1990
DOI: 10.1007/bf01293076
|View full text |Cite
|
Sign up to set email alerts
|

Load capacity and deflection of fire-resistant steel beams

Abstract: The methodology of defining safety of constructions in fire has not yet been sufficiently verified and agreed upon. This paper includes calculation results for steel beams, which prove that the ultimate load-bearing capacity predicted by plastic design theory, which is valid in engineering calculations, is not sufficient for determining the critical temperature. The reason is that this temperature tends to be limited in some cases by large deflections of beams in fire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Such large deflections in beams might also lead to loss of fire compartmentation, and thus facilitate the spread of fire between compartments either horizontally or vertically. Therefore, applying the strength limit state alone, which is generally achieved after undergoing large deflections and rotations, to evaluate fire resistance of restrained steel beams, may not reflect realistic assessment of failure [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Such large deflections in beams might also lead to loss of fire compartmentation, and thus facilitate the spread of fire between compartments either horizontally or vertically. Therefore, applying the strength limit state alone, which is generally achieved after undergoing large deflections and rotations, to evaluate fire resistance of restrained steel beams, may not reflect realistic assessment of failure [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The definition of critical temperature was firstly proposed by Skowronski [2] based on the design for both ultimate limit state (ULS) and serviceability limit state (SLS). It was concluded that, in most fire situations, the critical temperature in ULS would govern the failure mode; but for long beams as well as beams designed with a large margin of safety for room temperature, they might fail due to an abrupt increase of deflection but the stresses remained small.…”
Section: Introductionmentioning
confidence: 99%